Effects of use of PFA on strength of stone column and sand column - Shakri M.S.; Hafez M.A.; Adnan M.A.; Nazaruddin A.T. (E-Journal of Geotechnical Engineering, 2023)
The ground improvement techniques have been designed to address problems related to weak soft ground. The techniques such as stone column and sand column have been chosen since many years ago for solving the problems and subsequent construction work can be proceeded. No doubt these techniques have been widely used and help in the construction field but lately there are problems and issues particularly related to cost and how construction can help address environmental problems. Thus by use waste material Pulverized Fuel Ash (PFA) has been studied to solve the problems and issues related to. Unconfined Compression Test (UCT) had been conducted on both stone column and sand column and study has shown promising results. For stone column by using PFA between 60% to 70% giving the optimum UCS with the highest was recorded 2.44 MPa for 5% cement used and 4.23 MPa for 10% cement used. While for sand column, the result showed almost same as stone column where the range of PFA used that giving the optimum UCS was between 50% to 70%. By using PFA 50% with 4% cement, result was recorded at 1.169 MPa UCS and for 8% cement and PFA 50% giving the result at 4.200 MPa UCS. For PFA 50% and cement 12%, result was recorded at 7.524MPa and for PFA 60% and 16% cement the result was recorded at 11.769 MPa. Other than PFA and cement, sand also used as a material in the study and all the sample have been cured for 28 days before test be conducted. No comparison between stone column and sand column conducted because both were use different proportion apart because both are different technique and back to the objective of this study conducted to focus on the effect of PFA on the stone column and sand column. © 2014 ejge.